“Albert’s soul looked forth from the organs of Madeline”: Anticipating Transness in William Godwin Jr.’s Transfusion (1835) - Clewes, Simon (Romanticism on the Net)

(untitled) (Université de Montréal, 2021)
This article examines William Godwin Jr.’s only novel Transfusion (1835) as an anticipation of transness. Building on existing scholarship that argues Godwin Jr. as attempting to remedy his position as an outsider to the Godwin-Shelley circle through presenting biological, familial ties as inviolable, this article extends the conversation to how the fixity of blood ties also informs his presentation of the fixity of biological sex. Albert’s transfusion of his soul into the body of his sister Madeline proves fatal: employing trans theory, primarily Judith Butler’s Bodies That Matter, I argue the author affirms fixed sexual boundaries by presenting a female/male fusion as being inherently destructive, diseased, and ultimately unlivable. I then document how this contrasts with Godwin Jr.’s half-sister Mary Wollstonecraft Shelley’s interrogation and destabilisation of sexual boundaries in Frankenstein (1818) through analysing Victor’s creation—and destruction—of the Female Creature. While Godwin Jr.’s entity dies directly as a result of an intrinsic and unavoidable “failing mechanism” within the body itself, the Female Creature’s extrinsic and avoidable death comes about because of Victor’s fear that she may “refuse to comply” with the narrowly defined, deterministic role he designates for her as being only a romantic partner for the Creature.